Hydro-adsorption sstudy by dynamic laser speckle of natural zeolite for adsorbent and fertilizer applications - Mojica Sepulveda, Ruth Dary (2016)
The dynamic behavior caused by hydro-adsorption process of materials based on a rich mineral clinoptilolite together with their acidic, basic and calcinated forms has been studied by the dynamic laser speckle (DLS) technique. We propose a modified Peleg’s equation to improve fitting of DLS data. Textural (BET), structural (XRD) and spectroscopic (FTIR) properties were also studied and compared. We demonstrated that DLS was the most sensitive, simple and inexpensive method for comparing the performance of adsorptive materials with slightly modified surfaces. It also allowed the correlation with physicochemical properties.